A SNP genetic linkage map based on the 'Hamilton' by 'Spencer' recombinant inbred line population identified QTL for seed isoflavone contents in soybean. Issue 5 (14th August 2015) - Akond, Masum; Liu, Shiming; Kantartzi, Stella K.; Meksem, Khalid; Bellaloui, Nacer; Lightfoot, David A.; Yuan, Jiazheng; Wang, Dechun; Anderson, James; Kassem, My Abdelmajid; Singh, R.
Abstract Soybean is one of the most important crops worldwide for its protein and oil as well as the health beneficial phytoestrogens or isoflavone. This study reports a relatively dense single nucleotide polymorphism (SNP)‐based genetic map based on 'Hamilton' by 'Spencer' recombinant inbred line population and quantitative trait loci (QTL) for seed isoflavone contents. The genetic map is composed of 1502 SNP markers and covers about 1423.72 cM of the soybean genome. Two QTL for seed isoflavone contents have been identified in this population. One major QTL that controlled both daidzein (qDZ1) and total isoflavone contents (qTI1) was found on LG C2 (Chr 6). And a second QTL for glycitein content (qGT1) was identified on the LG G (Chr 18). These two QTL in addition to others identified in soybean could be used in soybean breeding to optimize isoflavone content. This newly assembled soybean linkage map is a useful tool to identify and map QTL for important agronomic traits and enhance the identification of the genes involved in these traits.